Effi Briest (1894): modernidade e tradição no romance de Theodor Fontane, em meio à unificação alemã - Moraes, Victor José Saris (2021)
This study analyzes the novel entitled Effi Briest (1894) written by Theodor Fontane (1819-1898) and published by Deutsche Rundschau in six episodes between 1894 and 1895 and as a book in 1895. The novel depicts the story of an adultery inside an originally Prussian family during the previous years of the German Unification in 1871. Fontane, besides living those events, produced the novel based on the memories of people who were close to the protagonist of the event and on the recovery of news from old newspapers which emphatically resounded the case at that time. But to clarify such a plot, Fontane enlightened all tensions between the new and the old, in other words, between the modernity which was imposed with the unification and the old and tradicional values, perceptible in the reactions of the different protagonists involved in those episodes. Thus, it is observed how private life could reflect moral and ethical values once it deals with people of substantial social representativeness at that moment revealing the tensions between tradition and modernity in that society at the moment of the German Unification